Electrospinning for Biomedical Applications - สุวรรณทอง, อรวรรณ (KKU Science Journal, 2015)
Electrospinning has been received much interest, since it is a simple and versatile process for fabricating continuous ultrafine fibers using electrical forces. The use of electrospun fiber mats in biomedical applications (i.e., tissue engineering, wound dressing, and drug delivery system) has been gained interest in the past several years due to its unique properties such as high surface area to mass/volume ratio, high porosity, and high mechanical properties. This review summarizes the background of electrospinning, factors affecting to electrospinning, polymers used in biomedical applications, and the use of electrospinning in biomedical applications such as tissue engineering, wound dressing, and drug delivery system.